Neuroprotective Effects of Overexpressing Tissue Inhibitor of Metalloproteinase TIMP-1 - Tejima, Emiri (Mary Ann Liebert, Inc., 2009)
Accumulating data suggest that matrix metalloproteinases (MMPs) may be important mediators in the pathophysiology of acute brain injury after trauma or stroke. Here, we test the hypothesis that the endogenous tissue inhibitor of metalloproteinase (TIMP-1) is neuroprotective in vitro and in vivo. For in vitro studies, primary cortical neuronal cultures were subjected to hypoxia and reoxygenation. Treatment with recombinant TIMP-1 protein significantly decreased neuronal death. In vivo studies in models of brain trauma and stroke supported these cell culture results. After controlled cortical impact, 24-h MMP-9 levels were significantly reduced in transgenic mice overexpressing TIMP-1 compared to wild-type mice. And at 7 days post-trauma, brain lesion volumes were also significantly decreased by TIMP-1 overexpression as well. In a model of transient 2-h focal cerebral ischemia, MMP-9 levels were lower in TIMP-1 transgenic mice compared with wild-types. Correspondingly, blood-brain barrier leakage was ameliorated by TIMP-1 overexpression, and 24-h infarction volumes were also reduced. Taken together, these cell culture and in vivo data provide initial proof-of-principle that TIMP-1 is neuroprotective against traumatic and ischemic brain injury in mice.